2021
DOI: 10.1016/j.biopha.2021.111384
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase-1 inducer hemin does not inhibit SARS-CoV-2 virus infection

Abstract: Antiviral agents with different mechanisms of action could induce synergistic effects against SARS-CoV-2 infection. Some reports suggest the therapeutic potential of the heme oxygenase-1 (HO-1) enzyme against virus infection. Given that hemin is a natural inducer of the HO-1 gene, the aim of this study was to develop an in vitro assay to analyze the antiviral potency of hemin against SARS-CoV-2 infection. A SARS-CoV-2 infectivity assay was conducted in V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The fact that viral protein expression was suppressed even when the cells had been treated with hemin after viral entry indicates that hemin may be able to suppress viral replication at the intracellular replication phase, similar to remdesivir 23 . However, a recent study suggested that HO-1 induced by hemin could not inhibit SARS-CoV-2 infection 24 . They demonstrated the unchanged viral RNA levels from the cell culture supernatants whereas we determined reduction of both viral RNA and viral protein in the cells after treatment with hemin.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that viral protein expression was suppressed even when the cells had been treated with hemin after viral entry indicates that hemin may be able to suppress viral replication at the intracellular replication phase, similar to remdesivir 23 . However, a recent study suggested that HO-1 induced by hemin could not inhibit SARS-CoV-2 infection 24 . They demonstrated the unchanged viral RNA levels from the cell culture supernatants whereas we determined reduction of both viral RNA and viral protein in the cells after treatment with hemin.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 virus (isolate NAVARRA-2473) [ 32 ] used for these assays was obtained in April 2020 from the nasal sample of a COVID-19 patient hospitalized in Clínica Universidad de Navarra, after obtaining the patient´s informed consent and Regional Government permits. We first grew the virus in confluent Vero-E6 cells (ATCC® CRL-1586™) and supernatants were collected at 72 h post-inoculation, when a clear cytopathic effect was evident.…”
Section: Methodsmentioning
confidence: 99%
“…However, the current literature regarding HO-1′s antiviral effect against SARS-CoV-2 remains unclear. Maestro et al showed that hemin does not inhibit SARS-CoV-2 viral replication in vitro [ 175 ]. Kidney epithelial Vero-E6 and lung Calu3 cell lines were treated with hemin and results showed that, despite a strong activation of HO-1 in both cell lines, there was no effect on SARS-CoV-2 viral replication, measured by the amplification of the N viral gene by RT-qPCR [ 175 ].…”
Section: Unveiling How Ho-1 Promotes Viral Clearancementioning
confidence: 99%
“…Maestro et al showed that hemin does not inhibit SARS-CoV-2 viral replication in vitro [ 175 ]. Kidney epithelial Vero-E6 and lung Calu3 cell lines were treated with hemin and results showed that, despite a strong activation of HO-1 in both cell lines, there was no effect on SARS-CoV-2 viral replication, measured by the amplification of the N viral gene by RT-qPCR [ 175 ]. However, a more recent report proposed hemin as a potential drug for treating COVID-19 via HO-1 induction [ 176 ].…”
Section: Unveiling How Ho-1 Promotes Viral Clearancementioning
confidence: 99%